Boron-Doped Single-Walled Carbon Nanotubes with Enhanced Thermoelectric Power Factor for Flexible Thermoelectric Devices - Liu, Ye; Khavrus, Vyacheslav; Lehmann, Thomas; Yang, Hong-Liu; Stepien, Lukas; Greifzu, Moritz; Oswald, Steffen; Gemming, Thomas; Bezugly, Viktor; Cuniberti, Gianaurelio (Giovanni) (ACS Applied Energy Materials, 2020)
We report a detailed experimental and theoretical study on thermoelectric properties of boron-doped single-walled carbon nanotubes (B-SWCNTs), which are versatile building blocks of flexible thermoelectric devices. Implantations of substitutional boron dopants (0.1-0.5 atom %) in SWCNTs are realized using thermal diffusion. The after-synthesis boron doping simultaneously improves the Seebeck coefficient (S) and electrical conductivity (σ) of SWCNT networks, leading to an S2σ value of 226 μW/mK2. First-principle calculations indicate that a few tenths atom % of substitutional boron atoms improve the S value of semi-conducting SWCNTs but reduce the electron conductance in individual SWCNTs. The high σ of B-SWCNT networks is attributed to the improved electrical transport between laterally contacted metallic and semi-conducting nanotubes. The produced B-SWCNTs are stable over high-temperature annealing or processing in liquid media, which inspired us to fabricate thermoelectric modules by a low-cost printing method. The modules demonstrate an increased thermoelectric efficiency by 76% compared to those with undoped SWCNTs. This work provides a feasible fabrication strategy and physical insights for B-SWCNT-based flexible thermoelectrics.
CRIS-Team Scopus Importer:2022-04-14
Keywords: ab initio stimulation; boron substitutional doping; flexible thermoelectric applications; single-walled carbon nanotubes; thermoelectric measurements